GDP Composition and Poverty: Evidence from Cross-Country Data - Joseph Casey Diego Banjarnahor; Rosma Indriana Purba; Ferry Vincenttius Ferdinand (Journal of Management Studies and Development, 2026)
This study examines whether the expenditure composition of gross domestic product (GDP) is systematically associated with poverty across countries, beyond the role of GDP levels alone. Using cross-country data from the World Bank’s World Development Indicators for the period 2000–2024, the study analyzes the relationship between poverty rates and the shares of consumption, investment, government spending, and net exports in GDP. The empirical approach combines descriptive statistics, Pearson correlation analysis, and ordinary least squares regression based on long-run country averages, with log GDP per capita included as a control variable. The results indicate that countries with higher consumption shares tend to have higher poverty rates, while net export shares are negatively associated with poverty in bivariate analysis. However, after controlling income differences, the association between net exports and poverty becomes positive. Investment and government spending shares show weaker and less consistent relationships with poverty. Overall, the findings suggest that income remains the dominant factor associated with cross-country poverty differences, while GDP composition provides additional structural information related to poverty outcomes. The results should be interpreted as cross-country associations rather than causal effects.